2017
DOI: 10.5944/ap.14.2.20753
|View full text |Cite
|
Sign up to set email alerts
|

Españoles e Inmigrantes Latinoamericanos condenados por violencia de género: ¿Existe un perfil diferencial?

Abstract: ResumenDiversas investigaciones destacan el rol de las diferencias culturales y de los factores relacionados con la inmigración en la violencia contra la pareja. El objetivo de este trabajo era analizar si existe un perfil diferencial entre hombres maltratadores españoles (n = 400) e inmigrantes latinoamericanos (n = 117). Para ello se seleccionaron variables según el modelo ecológico y se contrastaron ambos grupos mediante ANOVAs, MANOVAs y Chi-cuadrados. Los resultados obtenidos indicaron diferencias signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…Our results show differences among the participants in terms of their awareness of violence against their partners, the characteristics of each individual, the circumstances of each family, and the particularities of each culture and/or subculture. This finding is congruent with previous studies that have pointed out the existence of differential profiles among different groups of batterers (Fowler & Westen, 2011;Holtzworth et al, 1994;Llor-Esteban et al, 2016), with significant differences in variables such as age, level of education, economic and labor activity and other contextual variables (Herrero et al, 2016;Vargas et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results show differences among the participants in terms of their awareness of violence against their partners, the characteristics of each individual, the circumstances of each family, and the particularities of each culture and/or subculture. This finding is congruent with previous studies that have pointed out the existence of differential profiles among different groups of batterers (Fowler & Westen, 2011;Holtzworth et al, 1994;Llor-Esteban et al, 2016), with significant differences in variables such as age, level of education, economic and labor activity and other contextual variables (Herrero et al, 2016;Vargas et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the social support system in formal and informal systems, our results coincide with the study conducted by Vargas et al (2017) in which respondents have perceived, in general, less social support. Finally, at this level, it has been observed that the presence of cognitive distortions implies the consideration of women as inferior and vulnerable.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the complaints filed by women victims of Intimate Partner Violence, 49,904 (31.5%) were made by immigrant women (Observatorio contra la Violencia Doméstica y de Género y Consejo General del Poder Judicial, 2019). These data highlight the possibility of some differential factors of Intimate Partner Violence appearing in the immigrant population (Cummings, González-Guarda & Sandoval, 2013;Vargas, Lila, Catalá-Miñana & Gracia, 2017).…”
Section: Introductionmentioning
confidence: 63%
“…In addition to inconsistent evidence for the effectiveness of culturally-oriented BIPs in both Spain and elsewhere, very few studies have analysed the role of cultural belonging in BIPs despite the marked presence of men from various ethno-cultural origins, especially from the Latin American culture (Echauri, Fernández-Montalvo, Martínez & Azkarate, 2013;Fernández-Montalvo, Echauri, Martínez, Azcárate & López-Goñi, 2015;Vargas, Lila & Catalá-Miñana, 2015;Vargas, Lila, Catalá-Miñana & Gracia, 2017;Welland & Ribner, 2010). This work aimed to determine whether there were differences in the effectiveness of a standard BIP in Spain (i.e., cognitive-behavioural with motivational strategies and with no specific cultural adjustment) by comparing the treatment outcomes of Spanish and Latin American immigrant batterers.…”
Section: Introductionmentioning
confidence: 99%